Sistem Absensi dengan OpenCV Face Recognition dan Raspberry Pi - Astrid Nabila Prima; Cipto Prabowo; Rasyidah (SOTVI - Society of Visual Informatics, 2020)
Attendance data collection activities are routine. In general, this is done by signing an attendance sheet. This is considered slow and also causes disruption in carrying out lectures and activities. One solution to the problem is to use Face Recognition, Face Recognition is a biometric technology that has been widely applied in security systems in addition to eye retina recognition, fingerprint and iris recognition. In the application itself, face recognition uses a camera to capture a person's face and then compare it with faces that have previously been stored in a certain database. In the manufacturing process, Raspberry pi is used as the core of this tool. With the three things above, namely Attendance, Face Recognition, and Raspberry pi, a tool is formed that can meet the needs of an automatic, effective, and efficient attendance process